Y Soft Campus - poloopuštěný areál Střelnice v Brně-Pisárkách - Lysá, Karolína (Vysoké učení technické v Brně. Fakulta architektury)
Na jedné straně klidná lokalita obklopená lesy v těsné blízkosti s centrem Brna. Na straně druhé ambiciózní mladá firma specializující se na software a hardware pro tisk, kopírování a skenování. Interference nejnovějších technologií a přírody. Hledání moderního pojetí pracovního místa a s ním spojených benefitů, které přilákají další perspektivní zaměstnance. Důraz na ekologii projektu. Udržení rekreačního charakteru lokality. Práce s poměrně svažitým terénem a s orientací ke světovým stranám dle zadaných požadavků.

On one side a quiet location surrounded by forests in close proximity to the center of Brno. On the other hand, an ambitious young company specializing in software and hardware for printing, copying and scanning. Interference of the latest technologies and nature. Finding a modern job concept and the benefits associated with it that attract other prospective employees. Emphasis on project ecology. Keeping the recreational character of the site. Work with relatively sloping terrain and with orientation to the world sides according to the requirements.
Y Soft Campus - the semi-abandoned shooting range area in Brno-Pisarky
Keywords: brownfield; udržitelný rozvoj; administrativní budova; brownfield; sustainable development; administration building